Diseño de un pasteurizador de leche de 100 litros para la alimentación de terneros. - Quirola Manchay, Santiago David (2022)
In the present work, a design of a pasteurizing equipment for feeding calves was proposed as an alternative for farmers to raise calves until weaning, which can be approximately 45 to 75 days. Establishing important characteristics such as: the milk pasteurization cycle, avoiding contamination in the pasteurization process at the place of treatment and portability to the place of feeding necessary for the calves, minimizing contact with any contaminating element. Through the designated capacity of 100 liters, each element could be sized for the established functions such as: the practicality and feasibility of the design, the heating system, the agitation system and the dosing pump. With all the elements formed, it was possible to establish a relevant design proposal so that its construction can be carried out. For the temperature control and the desired operating system, the temperature of 65 °C was considered for 30 minutes, for which a PID control was established that allows the stability of the process. Consequently, a stirring system was proposed with the use of a frequency variator. As well as the proposal of a dosing system by means of a pump regulated by the desired flow from 1 liter to the amount as required. Likewise, in the control of the pasteurization, shaker and milk dosing system, the use of an S7-200 PLC was considered, which has the characteristics required for the fulfillment of the different functions. Finally, an autonomy of 4 hours is proposed for operation with the use of the rechargeable battery, which will allow freedom of mobility when feeding the calf in the specific place where the calves are. Key words: calf feeding, milk dosing, farmers, milk, pasteurization.